RIPK1–RIPK3–MLKL-Associated Necroptosis Drives Leishmania infantum Killing in Neutrophils - Barbosa, Laiana A.; Fiuza, Paloma P.; Borges, Letícia J.; Rolim, Fellipe A.; Andrade, Mayara B.; Luz, Nivea F.; Quintela-Carvalho, Graziele; Lima, Jonilson B.; Almeida, Roque P.; Chan, Francis K.; Bozza, Marcelo T.; Borges, Valeria M.; et al. (Frontiers in Immunology, 2018)
Necroptosis is a pro-inflammatory cell death, which happens in the context of caspase-8 inhibition, allowing activation of the receptor interaction protein kinase 1- receptor interaction protein kinase 3 - mixed lineage kinase domain-like (RIPK1-RIPK3-MLKL) axis. Recently, necroptosis has emerged as a key component of resistance against pathogens including infected macrophage by Leishmania infantum, the ethiologic agent of Visceral leishmaniasis (VL). VL is the most severe form of Leishmaniasis, characterized by systemic inflammation and neutropenia. However, the role of neutrophil cell death in VL has not been characterized. Here, we showed that VL patients exhibited increased Lactate dehydrogenase (LDH) levels in the serum, a hallmark of cell death and tissue damage. We investigated the effect of necroptosis in neutrophil infection in vitro. Human neutrophils pretreated with zVAD-fmk (pan-caspase inhibitor) and zIETD-fmk (caspase-8 inhibitor) increased ROS level in response to Leishmania infection, which is associated with necroptotic cell death. MLKL, an important effector molecule downstream of necroptosis pathway, was also required for Leishmania killing. Moreover, in absence of caspases-8, murine neutrophils displayed loss of membrane integrity, higher levels of reactive oxygen species (ROS) and decreased L. infantum viability. Pharmacological inhibition of RIPK1 or RIPK3 increased parasite survival when caspase-8 was blocked. Electron microscopy assays revealed morphological features associated with necroptotic death in L. infantum infected-neutrophils pretreated with caspase inhibitor, whereas infected cells pretreated with RIPK1 and RIPK3 inhibitors did not show ultra-structural alterations in membrane integrity and presented viable Leishmania within parasitophorous vacuoles. Taken together, these findings suggest that inhibition of caspase 8 contributes to elimination of L. infantum in neutrophils by triggering necroptosis. Thus, targeting necroptosis may represent a new strategy to control Leishmania replication.